Comparison of Two PCR Primer Sets for In-House Validation of GHSR Gene Variation Detection Employing Artificial Recombinant Plasmid Approach - Ahsanal Kasasiah; Jekmal Malau; Sekar Andjung Tresnawati; Priscinya Christiana Debora; Nur Komala Fitri; Saarah Hamidah Asmara Indratno; Asman Hitopik; Eriyanti Astika; Anisa Aula Rahma; Fikri, Al Mukhlas (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2024)
Stunting is a significant global public health problem caused by long-term dietary deficits that affect many children worldwide. Both environmental and genetic factors, including variants in the GHSR gene, play a crucial role in stunted growth. This study used an artificial recombinant plasmid DNA method to evaluate two primer set combinations for identifying DNA variants in the GHSR gene. Selecting suitable primer sets for identifying GHSR genetic variants linked to stunting is essential, as evidenced by PCR and sequencing techniques. The target gene, based on the GHSR reference sequence, consists of eight DNA variations (ΔQ36, G57G, P108L, L118L, R159R, C173R, D246A, and A277P). A recombinant plasmid was created by inserting a 1000 bp fragment of the GHSR gene into the pUC57 backbone. Primer sets were chosen based on their capacity to amplify these eight genetic variations and were optimized and validated using PCR methods. PCR and bi-directional sequencing verified the existence of surrounding DNA and specific single nucleotide variants (SNVs). In our study, we discovered four changes in the DNA sequence (R159R G>A, C173R T>C, D246A A>C, and A277P G>C) using the E1_F2/E1_R3 primer pair. Additionally, a new combination of primers (E1_F1/E1_R3) effectively detected seven DNA sequence mutations (ΔQ36 del CAG, G57G C>T, P108L C>T, L118L C>T, R159R G>A, C173R T>C, and D246A A>C). We have developed a new combination of forward and reverse primers to identify seven SNVs in the GHSR gene, which could serve as a diagnostic tool in clinical laboratory settings.